2017
DOI: 10.1002/jhbp.466
|View full text |Cite
|
Sign up to set email alerts
|

Survival rates after liver transplantation using hypertensive donor grafts: an analysis of the Scientific Registry of Transplant Recipients database

Abstract: The present study shows that graft and patient survivals were lower in recipients of hypertensive donor grafts, and highlights the importance of appropriately screening donors for HTN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…In comparison, Hu et al . [ 33 ] reported a much lower 5-year survival rate of 39.2% among postliver transplant patients. This discrepancy in findings may once again be due to age differences between cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, Hu et al . [ 33 ] reported a much lower 5-year survival rate of 39.2% among postliver transplant patients. This discrepancy in findings may once again be due to age differences between cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Alamo et al [ 13 ] found donor hypertension was suggestive of poor prognostic factors in liver transplant recipient survival. Recently, in an analysis of the SRTR database, Hu et al [ 25 ] found that liver transplant recipients of HTN donor grafts have poorer graft and patient survival than those of non-HTN donor grafts. However, in the present study, we found that having a donor with hypertension is not a poor prognostic factor for patient survival and liver graft survival in SLKT recipients.…”
Section: Discussionmentioning
confidence: 99%